The performance of removal phosphorus - Adnan, Suraya Hani; A. Roni, Norwardatun; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2020)
Turphorus is an important nutrient constituent for aquatic plant growth in the natural water system. However, excessive phosphorus loads in water bodies due to industrial, agricultural and household wastes might cause the overgrowth of aquatic plants or algae. This will accelerate the depletion of dissolved oxygen (DO) in water and lead to eutrophication. Hence, strict effluent quality standards for wastewater treatment plants (WWTPs) are implemented by governments all over the world [13]. Municipal wastewaters comprehend from 5 to 20 mg/L of total phosphorus, of which 1-5 mg/l are organic and the rest are inorganic. Phosphorus is one of the main constituents of synthetic detergents. The individual phosphorus impact varies between 0.65 and 4.80 g/inhabitant per day with an average of about 2.18 g. Generally, secondary treatment can only remove 1-2 mg/L of phosphorus, so excess phosphorus is often discharged in the final effluent and causes eutrophication in surface water [9]. [5] found that the addition of phosphorus in the range of even 0.1-5.6 µ/L over a long period might activate algal blooms in part of a natural lake. Therefore, phosphorus removal from wastewater is important. To remove phosphorus, it must either be rehabilitated into a particulate form or removed as a particulate by sedimentation or filtration using membrane treatment. The most regularly used method for phosphorus removal from wastewater is chemical precipitation and this method is able to reduce the concentration of phosphorus to values below 1 mg/L in sewage treatment plants. Nevertheless, chemical precipitation is expensive in many parts of the world and it might produce new pollutants such as chloride and sulphate [4]. In addition, it also requires the disposal for the precipitate formed and neutralisation of the treated effluent.